Identifikasi Perilaku Dan Karakteristik Awal Peserta Didik (Konsep dan Pola Penerapan Dalam Desain Instruksional) - Rahmat Rifai Lubis (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
Identifying the early behavior and characteristics of learners is a process that teachers must pass through in designing their learning. This is especially important to determine the starting point of learning materials. In addition, this process also aims to avoid the occurrence of two things in the class, namely saturation and difficulty. Students who have mastered the material taught will certainly feel saturated, because it felt the material was repeated, while students who have no basis at all of the material will certainly feel the difficulties and even despair of the material being taught. In addition, this process also makes teachers understand the external factors that affect the learners in receiving lessons.